Status, mechanism, suitable distribution areas and protection countermeasure of invasive species in the karst areas of Southwest China - Li, Yonghua; Song, Tianjian; Lai, Yangjun; Huang, Yuxin; Fang, Lei; Chang, Jiang (Frontiers in Environmental Science, 2022)
Biological invasion is one of the major threats to global biodiversity attracting a primary focus of scientific attention. During the past decades, due to the diversity and peculiarity of species, coupled with the vulnerable ecosystem, karst areas have received more and more attention. Numerous investigations and studies have confirmed that the karst areas in Southwest China are suffering from biological invasions under the intensified human activities and the climate change they caused. Despite some fundamental research on invasive species that has been conducted to understand the species and distribution in the karst areas, the mechanism of biological invasions and the response of karst ecosystem are still lack sufficient knowledge. In this paper, we summarized the habitat characteristics and invasion status of karst areas to biological invasions. This paper comprehensively analyzed the research results on biological invasions in karst areas to understand the status and development trends of biological invasions in the karst of China, so as to promote the relevant research on biological invasions in the karst areas. We found that the biological invasions in the karst areas were increasing with years. We also revealed the possible mechanism including competition, mutualism, allelopathy and phenotypic plasticity of biological invasion in karst by summarizing the relevant research results of in the karst areas. Moreover, the response of karst to biological invasion was described from the aspects of ecosystem, community, species and genetic levels, etc. By comparing the characteristics of invasive species that have been found in karst area, we analyzed the common characteristics including strong fecundity and rapid growth rate, strong environmental adaptability, strong phenotypic plasticity and high genetic diversity of the existing invasive species, we simulated and predicted the habitat of invasive species. Overall, we found three areas with high habitat suitability covering Chinese southwest Karst ecosystem, which include the southern Yunnan-Guizhou Plateau, foothill area on the Min-Yue-Gui and foothill area of southern Yunnan. It is also worth noting that the Sichuan Basin has a higher invasive risk compared to its surrounding Karst ecosystem, mainly because of the high habitat suitability of some invasive species. Therefore, we suggest that a general survey of alien invasive species in the karst areas of Southwest China should be carried out as soon as possible, focusing on the survey of the suitable areas of alien species for early warning. In addition, to establish a database of invasive alien species in the karst areas of southwest China, strengthen the monitoring of alien species, and evaluate the impact of invasive species in key areas on the biodiversity and ecosystem in the karst areas of Southwest China, so as to maintain the stability of cave biodiversity and the fragile ecosystem.